2017
DOI: 10.1242/jeb.167742
|View full text |Cite
|
Sign up to set email alerts
|

Myosin phosphorylation potentiated steady state work output without altering contractile economy of mouse fast skeletal muscles

Abstract: Skeletal myosin light chain kinase (skMLCK)-catalyzed phosphorylation of the myosin regulatory light chain (RLC) increases (i.e. potentiates) mechanical work output of fast skeletal muscle. The influence of this event on contractile economy (i.e. energy cost/work performed) remains controversial, however. Our purpose was to quantify contractile economy of potentiated extensor digitorum longus (EDL) muscles from mouse skeletal muscles with (wild-type, WT) and without (skMLCK ablated, skMLCK) the ability to phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…From the perspective of the active state in a muscle the twitch is a submaximal response (vs. a tetanus) and potentiation is defined as the transient enhancement of both twitch peak torque and maximal rate of torque development (RTD) following a CC (Sale, 2002). This transient muscular facilitation can increase twitch torque upwards of ∼200% (Baudry & Duchateau, 2004; Smith et al., 2011) and following an isometric CC is maximal immediately and follows an exponential decay to baseline levels within ∼30 s to ∼10 min depending on the muscle and degree of PAP induced (Baudry & Duchateau, 2004; Gittings et al., 2018; Hamada et al., 2003; MacIntosh & Gardiner, 1987; MacIntosh et al., 2008; Seitz et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the active state in a muscle the twitch is a submaximal response (vs. a tetanus) and potentiation is defined as the transient enhancement of both twitch peak torque and maximal rate of torque development (RTD) following a CC (Sale, 2002). This transient muscular facilitation can increase twitch torque upwards of ∼200% (Baudry & Duchateau, 2004; Smith et al., 2011) and following an isometric CC is maximal immediately and follows an exponential decay to baseline levels within ∼30 s to ∼10 min depending on the muscle and degree of PAP induced (Baudry & Duchateau, 2004; Gittings et al., 2018; Hamada et al., 2003; MacIntosh & Gardiner, 1987; MacIntosh et al., 2008; Seitz et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, H-YPLP upregulated the expressions of Acta1, triadin, Flnc, and Mylpf (Table ). Previous research has shown that the phosphorylation of the myosin regulatory light chain could enhance the dynamic contractile of the fast myofiber . Moreover, actin was downregulated by exercise fatigue in rat skeletal muscle .…”
Section: Resultsmentioning
confidence: 91%
“…Previous research has shown that the phosphorylation of the myosin regulatory light chain could enhance the dynamic contractile of the fast myofiber. 35 Moreover, actin was downregulated by exercise fatigue in rat skeletal muscle. 16 Lee et al 36 found the supplement of lignan-rich nutmeg extract upregulated the Acta1 expression in muscle tissue of aged mice.…”
Section: Analysis Of Daps Between H-yplp and Nc Groups The Informatio...mentioning
confidence: 99%
“…However, it is most effective after short (5 s)-duration contractile activity 8) . The proposed mechanisms under-*Correspondence: tomoyan0122@yahoo.co.jp lying post-activation potentiation are associated with phosphorylation of myosin regulatory light chains [9][10][11] and increased recruitment of higher-order motor units 12,13) . However, less is known about the involvement of the motor cortex in post-activation potentiation.…”
Section: Introductionmentioning
confidence: 99%